The construction of identity in haitian indigenism and the post-colonial debate - Déus,Frantz Rousseau (2020)
Abstract This article focuses on three moments in the intellectual elucidation of Haitian identity during the time that Haiti was occupied by the United States, from 1915 to 1934. It analyses the intellectual output of writers of Haitian Indigenism, which emerged during this period of crisis and its political developments. The article makes five main points: first, it presents the emergence of Haitian Indigenism; second, it turns to the first manifestation of Haitian intellectuals against the US occupation, considering the so-called ‘writers at the margins of Indigenism; third, it presents the position of authors of the Revue Indigène, particularly of Jean Price-Mars; fourth, it analyses the Revue Les Griots, concentrating on how François Duvalier makes political use of the racial issue. Finally, through these investigations, the article establishes a dialogue with contemporary authors who discuss the construction of identity within post-colonial debate.